(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Comparative analysis of horticultural characteristics of samples of imported and local pea varieties and the use of advanced foreign and local science, techniques and innovative agrotechnologies in pea cultivation are considered very important. For this reason, this article provides information on the comparative analysis of pea seeds in the laboratory with determination of their germination.